PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BERBASIS PROBLEM BASED LEARNING PADA MATERI GAYA DAN GERAK UNTUK SISWA KELAS IV SD: DEVELOPMENT OF MULTIMEDIA LEARNING BASED ON PROBLEM BASED LEARNING ON FORCE AND MOTION MATERIAL FOR CLASS IV PRIMARY STUDENTS - Darmono, Al; Dhian Dwi Nur Wenda (Kurikula : Jurnal Pendidikan, 2024)
This research aims to develop multimedia learning based on problem based learning on force and movement material for fourth grade elementary school students. The method used in this research is the research and development or R&D method. Meanwhile, the research model used refers to the ADDIE research model. The ADDIE model has five stages, namely, Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at SDN Mojoroto 4, Kediri city with a total of 26 students as test subjects. The research instruments used in this research were observation guidelines, expert validation sheets, teacher response questionnaires and test questions. Based on the results of the data analysis that has been carried out, the level of validity, practicality and effectiveness of the product can be determined. The average product validity test results obtained a score of 87.5% with very valid criteria, the product practicality test results based on teacher responses obtained a score of 94% with very practical criteria, while the product effectiveness test results showed that the learning multimedia developed was effectively used to improve results. Student learning on force and motion material shows a student classical score of 84. Based on the results of the research and development that has been carried out, it can be concluded that the product developed is suitable for use in science learning in elementary schools.